Physical Activity, Sedentary Behavior, and Barriers to Exercise in People Living With Dystonia - McCambridge, Alana; Meiring, Rebecca M.; Bradnam, Lynley V. (Frontiers in Neurology, 2019)
Background: Dystonia is a neurological movement disorder that presents as sustained or intermittent involuntary muscle contractions causing abnormal postures and movements. Knowledge of dystonia is mostly at the impairment level with minimal understanding of activity and participation limitations. Physical activity (PA) is an important aspect of neurological disease management, with wide-ranging benefits for overall health and quality of life. No studies have quantified PA and sedentary behavior (SB), nor explored barriers to being physically active in people with dystonia. Methods: Participants diagnosed with any form of dystonia completed a mixed-methods anonymous online survey on activity behaviors. The International Physical Activity Questionnaire (IPAQ) and Adult Sedentary Behavior Questionnaire (SBQ) assessed self-reported PA and SB. Barriers to exercise engagement were investigated according to the five-factor social-ecological framework and dystonia-specific questions regarding the impact of exercise on symptoms were included. Results: Two-hundred and sixty-three participants consented to the study (mean (SD) age = 55 (13) years, 76% Female). A large proportion of respondents (40%) reported living with cervical dystonia (CD). Overall, the median (IQR) time spent in walking, moderate, and vigorous activity was 60 (0–120), 120 (15–300), and 0 (0–13) min/day, respectively. SB time during weekdays was 285.0 (157.5–465.0) min/day and 345.0 (195.0–502.5) min/day on weekends. Fifty-five percent of participants were dissatisfied with their current level of PA and 75% reported dystonia had decreased their level of PA. Fifty-seven percent found their symptoms were worsened during exercise though the after-effects on symptoms varied. Fatigue, motor symptoms, pain, and poor balance were commonly cited limiting factors. Qualitative and quantitative data indicated difficulties with more vigorous intensity activity. The common barriers to engagement were personal and governmental factors, such as physical impairments, lack of funding and lack of trained exercise professionals. Conclusion: While more than half of respondents indicated they were not satisfied with their current level of PA, and exercise primarily worsened their dystonia symptoms, most participants were meeting the minimum guidelines. Future studies should incorporate robust objective methods of PA and SB measurement and explore the causal mechanisms underpinning exercise-induced aggravation of dystonic symptoms to further enhance life participation of people living with dystonia.